What drives the radio slopes in radio-quiet quasars?. Issue 4 (16th November 2018) - Laor, Ari; Baldi, Ranieri D; Behar, Ehud
ABSTRACT: The origin of the radio emission in radio-quiet (RQ) quasars is not established yet. Important hints can be provided by the spectral slope, and its relation to other emission properties. We compiled the highest resolution 5 and 8.4 GHz Very Large Array observations available of the RQ optically selected Palomar–Green (PG) quasars atz < 0.5. We derive the 5–8.4 GHz spectral slope, αR, for 25 of the complete and well-studied sample of 71 RQ PG quasars. We find a highly significant correlation of αR with L / L Edd, where high L / L Edd (>0.3) quasars have a steep slope (αR < −0.5), indicative of an optically thin synchrotron source. In contrast, lower L / L Edd (<0.3) quasars generally have a flat slope (αR > −0.5), indicative of a compact optically thick synchrotron source. Flat αR quasars also have a low Fe ii /Hβ line ratio, and a flat soft X-ray slope. The 16 radio loud (RL) PGs do not follow the RQ quasar set of correlations, and their αR is set by M BH, suggesting that the radio emission mechanisms in RL and RQ quasars are different. A possible interpretation is that high L / L Edd RQ quasars produce a strong outflow and an associated optically thin synchrotron emission. In lower L / L Edd RQ quasars, the strong outflow is missing, and only a compact optically thick radio source remains, possibly associated with the accretion disc coronal emission. A systematic study of RQ quasars at higher frequencies, and higher resolution, can test whether a compact flat source indeed resides in the cores of all RQ quasars, and allows the exploration of its relation with the coronal X-ray emission.